Educating our youth to care about each other and the world - Schleicher, Andreas (Education and skills today)
by Andreas Director, Directorate for Education and Skills In 2015, 193 countries committed to achieving the 17 Sustainable Development Goals (SDGs) of the United Nations, a shared vision of humanity that provides the missing piece of the globalisation puzzle. The extent to which that vision becomes a reality will in no small way depend on what is happening in today’s classrooms. Indeed, it is educators who hold the key to ensuring that the SDGs become a real social contract with citizens. Goal 4, which commits to quality education for all, is intentionally not limited to foundation knowledge and skills, such as literacy, mathematics and science, but emphasises learning to live together sustainably. This has inspired the OECD Programme for International Student Assessment (PISA), the global yardstick for success in education, to include global competence in its metrics for quality, equity and effectiveness in education. PISA will assess global competence for the first time ever in 2018.